The development of global IPv6 products: an exploration. (11th November 2005) - Tseng, Shu-Fen; Lee, Hsi-Chieh; Kung, Te-Ching; Chou, Shou-Lien, Jing-Yi Chen
With the rapid development and enhancement of internet technology, the shortage of traditional IPv4 address has been gradually recognised. As we know, the invention of the new IP standard provides a solution to solve the problem of insufficient IP address. However, it is a costly and enduring process to migrate from the IPv4 to IPv6. By analysing worldwide IPv6-related products, we report Taiwan's strength and challenges in developing IPv6 and propose future development for industry and policy making.